2018
DOI: 10.1124/jpet.117.245506
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 2A Inhibitor TAK-915 Ameliorates Cognitive Impairments and Social Withdrawal in N-Methyl-d-Aspartate Receptor Antagonist–Induced Rat Models of Schizophrenia

Abstract: The pathophysiology of schizophrenia has been associated with glutamatergic dysfunction. Modulation of the glutamatergic signaling pathway, including -methyl-d-aspartate (NMDA) receptors, can provide a new therapeutic target for schizophrenia. Phosphodiesterase 2A (PDE2A) is highly expressed in the forebrain, and is a dual substrate enzyme that hydrolyzes both cAMP and cGMP, which play pivotal roles as intracellular second messengers downstream of NMDA receptors. Here we characterize the in vivo pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 63 publications
(92 reference statements)
0
14
0
Order By: Relevance
“…Hcyb1 produces neuroprotective and antidepressant‐like effects in mice [ 60 ]. TAK-915 shows efficacy in ameliorating cognitive and social impairment in induced rat models of SCZ [ 61 ] and it improves cognitive impairment associated with aging in mice [ 62 ]. To date, one phase I clinical trial has been reported for this compound (Supplementary Table V ).…”
Section: Introductionmentioning
confidence: 99%
“…Hcyb1 produces neuroprotective and antidepressant‐like effects in mice [ 60 ]. TAK-915 shows efficacy in ameliorating cognitive and social impairment in induced rat models of SCZ [ 61 ] and it improves cognitive impairment associated with aging in mice [ 62 ]. To date, one phase I clinical trial has been reported for this compound (Supplementary Table V ).…”
Section: Introductionmentioning
confidence: 99%
“…PDE2A is highly expressed in brain regions that are important for cognitive functions, including the cerebral cortex, hippocampus, and striatum (Stephenson et al, 2012;Kelly et al, 2014). In in vitro and in vivo animal studies, PDE2A-selective inhibitors enhanced long-term potentiation and improved the performance of multiple memory tasks (Boess et al, 2004;Domek-Łopaci nska and Strosznajder, 2008;Helal et al, 2018;Nakashima et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies provide evidence towards the role of TGF-β1 regulating synaptogenesis in cortical and thalamic neurons (Diniz et al, 2012 ; Bialas and Stevens, 2013 ). TGF-β signaling pathway plays a critical role in neuron specification and its disruption has been identified as one of the factors contributing to neurodevelopmental disorders such as schizophrenia (Yi et al, 2010 ; Nakashima et al, 2018 ). Apart from its role in synaptic growth, TGF-β signaling has been suggested to maintain synaptic homeostasis.…”
Section: Discussionmentioning
confidence: 99%